Ecological risk assessment for Pacific salmon exposed to dimethoate in California. (5th October 2016) - Whitfield Aslund, Melissa; Breton, Roger L.; Padilla, Lauren; Winchell, Michael; Wooding, Katie L.; Moore, Dwayne R. J.; Teed, R. Scott; Reiss, Rick; Whatling, Paul
Abstract: A probabilistic risk assessment of the potential direct and indirect effects of acute dimethoate exposure to salmon populations of concern was conducted for 3 evolutionarily significant units (ESUs) of Pacific salmon in California. These ESUs were the Sacramento River winter‐run chinook, the California Central Valley spring‐run chinook, and the California Central Valley steelhead. Refined acute exposures were estimated using the Soil and Water Assessment Tool, a river basin–scale model developed to quantify the impact of land‐management practices in large, complex watersheds. Both direct effects (i.e., inhibition of brain acetylcholinesterase activity) and indirect effects (i.e., altered availability of aquatic invertebrate prey) were assessed. Risk to salmon and their aquatic invertebrate prey items was determined to be de minimis. Therefore, dimethoate is not expected to have direct or indirect adverse effects on Pacific salmon in these 3 ESUs. Environ Toxicol Chem 2017;36:532–543. © 2016 SETAC